Left Atrial Cardiomyopathy – A Challenging Diagnosis - Kreimer, Fabienne; Gotzmann, Michael (Frontiers in Cardiovascular Medicine, 2022)
Atrial cardiomyopathy (ACM) has been an ongoing focus of research for several years. There is evidence that ACM is responsible for atrial fibrillation and embolic strokes of undetermined sources. Therefore, the correct diagnosis of ACM is of clinical importance. Various techniques, including electrocardiography, echocardiography, cardiac magnetic resonance imaging, computed tomography, electroanatomic mapping, genetic testing, and biomarkers, can both identify and quantify structural, mechanical as well as electrical dysfunction in the atria. However, the question arises whether these techniques can reliably diagnose ACM. Because of its heterogeneity, clinical diagnosis is challenging. To date, there are no recommendations for standardized diagnosis of suspected ACM. However, standardization could help to classify ACM more precisely and derive therapeutic directions to improve individual patient management. In addition, uniform diagnostic criteria for ACM could be important for future studies. Combining several parameters and relating them seems beneficial to approach the diagnosis of ACM. This review provides an overview of the current evidence regarding the diagnosis of ACM, in which several potential parameters are discussed and, consequently, a proposal for a diagnostic algorithm is presented.